RARE PRIMARY IMMUNODEFICIENCY – HYPER-IgE-SYNDROME: CASE REPORT AND LITERATURE REVIEW - Nikolai Vasil'evich Sobotyuk; E. A. Potrokhova; S. A. Golochalova; S. V. Bochantsev; T. N. Kharlamova; Y. A. Stroylova (Педиатрическая фармакология, 2013)
The article is dedicated to one of the rare primary immunodeficiency pathologies – hyper-IgE-syndrome. The authors present a clinical case from their own practice and a literature review on this disease. Inheritance, pathogenesis, clinical manifestations and hyper-IgE-syndrome diagnostics issues are also examined in the article. The article shows differences of disease course at different inheritance types – autosomal-dominant and autosomal-recessive.